2015
DOI: 10.3176/earth.2015.05
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructures of porostromate microproblematica from a Mulde Event (Homerian, Silurian) bioherm in Podolia, Western Ukraine

Abstract: The Mulde Event (Homerian, Wenlock) of the Silurian is characterized by a positive δ 13 C isotope excursion, a stepwise extinction of the hemipelagic fauna and an increase in non-skeletal deposits thought to be microbial, proliferating in shallow marine environments. There is little known about whether the proliferation of microbialites is due to reduced grazing, increased seawater saturation state or an increase in nutrient supply. We have studied a Mulde Event-associated buildup from the Muksha Formation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Although some have been tentatively counted among cyanobacteria, recent investigations of the ultrastructure of Wetheredella (Jarochowska & Munnecke ) and Hedstroemia (Castagner et al . ) have shown that both problematica secreted their calcareous skeletons in a biologically controlled manner, an argument against their microbial affinity.…”
Section: Discussionmentioning
confidence: 99%
“…Although some have been tentatively counted among cyanobacteria, recent investigations of the ultrastructure of Wetheredella (Jarochowska & Munnecke ) and Hedstroemia (Castagner et al . ) have shown that both problematica secreted their calcareous skeletons in a biologically controlled manner, an argument against their microbial affinity.…”
Section: Discussionmentioning
confidence: 99%